2010
DOI: 10.1007/s00018-010-0380-0
|View full text |Cite
|
Sign up to set email alerts
|

Structure and function of interleukin-22 and other members of the interleukin-10 family

Abstract: The IL-10 family of cytokines is comprised of IL-10, . The IL-10 family members bind to shared class II cytokine receptor chains that associate in various combinations in heterodimeric complexes. Upon interleukin/receptor complex formation, these proteins switch on the Jak/STAT pathway and elicit pleiotropic biological responses whose variety sharply contrasts with their structural similarities. IL-10 family members are involved in several human diseases and health conditions and hence their structural analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 172 publications
(345 reference statements)
0
31
0
Order By: Relevance
“…TNF-α mediates inflammatory reaction by altering the blood brain barrier, influences lymphocyte behavior, and induces tissue damage with astrogliosis and destruction of oligodendrocytes (Issazadeh et al, 1995;Montgomery and Bowers, 2012). The anti-inflammatory and immunoregulatory effect of IL-10 could be contributed to downregulation of Th1 inflammatory cytokines expression, enhancing B cell survival and antibody production, blocking NF-κB activity and promoting tissue repair (Trivella et al, 2010). The preliminary evidence showed that B cells from multiple sclerosis patients produce decreased amounts of IL-10 suggesting its regulatory role (Duddy et al, 2007).…”
Section: Discussionmentioning
confidence: 97%
“…TNF-α mediates inflammatory reaction by altering the blood brain barrier, influences lymphocyte behavior, and induces tissue damage with astrogliosis and destruction of oligodendrocytes (Issazadeh et al, 1995;Montgomery and Bowers, 2012). The anti-inflammatory and immunoregulatory effect of IL-10 could be contributed to downregulation of Th1 inflammatory cytokines expression, enhancing B cell survival and antibody production, blocking NF-κB activity and promoting tissue repair (Trivella et al, 2010). The preliminary evidence showed that B cells from multiple sclerosis patients produce decreased amounts of IL-10 suggesting its regulatory role (Duddy et al, 2007).…”
Section: Discussionmentioning
confidence: 97%
“…7,[51][52][53] Phylogeny of class II cytokines The phylogeny of class II cytokines has been the subject of substantial debate. 2,[11][12][13][14][15][16][17]22 Most of the conclusions were drawn from sequence alignments and subsequent calculation of phylogenetic trees.…”
Section: Structure Of Zil-22mentioning
confidence: 99%
“…Within the family of IL-10 cytokines, IL-22 is preferentially secreted by Th17 cells while IL-19, IL-20, and IL-24 are mostly produced by keratinocytes, secondarily to Th17-related cytokine stimulation [37,38]. All these cytokines were described to involve STAT3 signaling [39] and to play a redundant role in the alteration of epidermis functions [40], which might contribute together, with IL-6, to compensate the absence of OSM activity.The lack of requirement of OSM in the induction of the IMQ model could also be explained by its strong dependence on the IL-23/IL-17 axis [13]. Both cytokines were found upregulated in a similar manner in all groups of IMQ-treated mice.…”
mentioning
confidence: 99%